Mediating effect of social support on the relationships between caregiver burden and quality of life in family caregivers of people with dementia: a cross-sectional study in Rural China - Ying Hu; Xiajun Guo; Hui You; Li Liu; Yao Wang (BMC Nursing)
Abstract Background China has the largest percentage of people with dementia (PwD) around the world. And most of them are cared for by their family members. The purpose of this study was to identify the quality of life (QoL) of family caregivers of PwD in rural China and to investigate the mediating role of social support between caregiver burden and QoL under the guidance of a stress process model. Methods This cross-sectional design study in rural areas of Hunan province, China included 150 family caregivers of PwD. The participants completed questionnaires, including the demographic information questionnaire on caregivers and PwD, the caregiver version of QoL in Alzheimer’s Disease, the Caregiver Burden Inventory, and the Multidimensional Scale of Perceived Social Support. The demographic factors associated with QoL were subjected to univariate analysis. Pearson’s correlations were used to test the relationship among care burden, social support, and QoL. SPSS PROCESS Procedure was conducted to test the hypothesis of mediating effects. Results The family caregivers of PwD exhibited a fair QoL, with a score of 29.01 ± 4.059. Pearson’s correlations revealed the negative correlation of caregiver burden with social support and QoL and the positive correlation between social support and the QoL of family caregivers. The results suggest the mediating role of social support between caregiver burden and the QoL. Conclusion The QoL of family caregivers of PwD in rural China is suboptimal and indirectly influenced by the caregiving burden through the mediating effect of social support. Strengthening social support networks, both formal and informal, is essential to reducing caregiver burden and improving the QoL of family caregivers of PwD.